Properties of foam-mat dried Japanese threadfin bream [Nemipterus japonicus (Bloch, 1791)] minced meat powder - Mohamed, Abdulrahim Abubakar (2021)
This study aimed to determine the effect of drying temperature and amount of foaming agent incorporated on the properties of foam-mat dried (FMD) threadfin bream minced meat powder; and to evaluate the effect of the selected additives on the rheological properties of FMD fish powder by conducting the frequency sweep test. Japanese threadfin bream (Nemipterus japonicus) minced meat was mixed with methyl cellulose (MC) as a foaming agent at 0.0, 0.5, 1.0 and 1.5% w/w and dried at 70 and 80℃. The FMD fish powder was then transferred to bottles and stored at 4℃ until analysis. The fish powder was tested for proximate composition, lipid quality, physico-chemical and functional properties. Drying time was 3 h longer for 70℃ than 80℃ to achieve the same level of moisture content of 3 – 4.5%. The crude protein of the fish powder dried at 70°C (84.70) was significantly higher (p<0.05) than 80°C (81.25%) as well as the pH values. A significantly lower water activity (p<0.05) was observed for powder dried at 70°C than 80°C, and the water activity of all powders was ˂0.40. The fish powder had an attractive yellowish-brown color. The L*, a*, b* and whiteness values of the FMD fish powder were found to be in the range of 78.80 – 81.02, 1.67 – 2.90, 22.66 – 24.99 and 67.10 – 70.40, respectively. An increase in particle size was observed upon increased the drying temperature and MC concentration, and the values were 116.22 – 126.95 and 124.34 – 131.80 μm for powders dried at 70°C and 80°C, respectively. The powders showed good - fair flowability and are within the acceptable range. Both protein solubility and water holding capacity had an inverse correlation with the drying temperature (r = -0.943) and (r = -0.749), respectively. Increased drying temperature and decreased MC concentrations resulted in increased emulsification property. Gelation was only obtained in the control sample dried at 70°C. FMD threadfin bream meat powder dried at 70°C was observed to have less thiobarbituric acid reactive substances (TBARS) and free fatty acid (FFA) compared to powder dried at 80°C (p<0.05). On the overall, FMD threadfin bream meat powder dried at 70°C showed better properties. Next, the rheological properties (elastic and viscous), gel stability and gel attribute of FMD fish powder at 70°C were determined by adding various additives at different concentrations, which were sodium chloride (0.7, 1.4 and 2.1% w/w) and sodium triphosphate (0.2 and 0.4% w/w). The results revealed that the storage modulus (G') of the FMD fish powder added with any type of the additives was higher than the loss modulus (G''). The highest G' value was obtained from powder added with NaCl, indicating a higher and stronger structured network. FMD fish powder containing MC was found to have a low gel strength even when the selected additives were added, which sample with 1.5% MC displayed the lowest gel strength. A better gel quality was obtained from FMD fish powder containing 1.0% of MC added with 2.1% NaCl.